ANALGESIC EFFECT OF BILATERAL SUBCOSTAL TAP BLOCK AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Khan, Karima Karam; Khan, Robyna Irshad (Journal of Ayub Medical College Abbottabad, 2018)
Background: Pain after laparoscopic cholecystectomy is mild to moderate in intensity. Several modalities are employed for achieving safe and effective postoperative analgesia, the benefits of which adds to the early recovery of the patients. As a part of multimodal analgesia, various approaches of Transversus abdominis plane (TAP) block has been used for management of parietal and incisional components of pain after laparoscopic cholecystectomy. This study was designed to compare the analgesic efficacy of two different approaches of ultrasound guided TAP block, i.e., Subcostal-TAP block technique with ultrasound guided Posterior-TAP block for post-operative pain management in patients undergoing laparoscopic cholecystectomy under general anaesthesia. Methods: In this double blinded randomized controlled study, consecutive nonprobability sampling was done and a total of 126 patients admitted for elective laparoscopic cholecystectomy fulfilling the inclusion criteria were selected. After induction of general anaesthesia, patients were randomized through draw method and received either ultrasound guided posterior TAP block with 0.375% bupivacaine (20ml volume) on each side of the abdomen or subcostal TAP block bilaterally with the same. Up to 24 hours postoperatively, static and dynamic numeric rating pain scores were assessed. Results: We found statistically significant difference in mean static pain scores over 24 hours postoperatively in subcostal TAP group, suggesting improved analgesia. However, mean dynamic postoperative pain scores were comparable between the two groups. Whereas, patients in both groups were satisfied with pain management. Conclusions: Ultrasound guided subcostal TAP block provides better postoperative analgesia as compared to the Posterior TAP block in laparoscopic cholecystectomy. Otherwise both of the approaches improve patient outcomes towards early recovery and discharge from hospital. Keywords: Laparoscopic cholecystectomy; Postoperative pain; Subcostal TAP block; ultrasound